2019
DOI: 10.1080/09650792.2019.1566084
|View full text |Cite
|
Sign up to set email alerts
|

Benchlearning – an action research program for transforming leadership and school practices

Abstract: Development, Coaching. She has a background as a practitioner in school (teacher, principal, etc).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 27 publications
2
22
0
3
Order By: Relevance
“…Thus, our findings indicate the importance of a long-time perspective in school leadership training programmes. Our results also reinforce previous recommendations to include action research in school leaders' education to promote learning and better prepare school leaders for their assignments (Sappington et al 2010, Wood and Govender 2013, Aas et al 2019). However, the results also show that organising this kind of learning activity can be challenging and even provoke resistance.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, our findings indicate the importance of a long-time perspective in school leadership training programmes. Our results also reinforce previous recommendations to include action research in school leaders' education to promote learning and better prepare school leaders for their assignments (Sappington et al 2010, Wood and Govender 2013, Aas et al 2019). However, the results also show that organising this kind of learning activity can be challenging and even provoke resistance.…”
Section: Discussionsupporting
confidence: 89%
“…Bush (2012) as well as Korach and Cosner (2017) have also noted that ways to improve school leaders' development, particularly learning activities during their education, require substantially more research attention. Nevertheless, several studies have shown that learning activities grounded in problem-based learning and action research can promote school leaders' double-loop learning and actions based on new knowledge in their leading practice (Sappington et al 2010, Wood and Govender 2013, Aas et al 2019. Other recommended learning activities that may contribute to school leaders' learning and actions include group coaching, case study analysis and mentoring (Aas and Vavik 2015, Daresh 2004, Bush 2012, Ärlestig 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Leaders do not see reflections as something that is part of their daily leadership practice, but something that comes in addition. Critical friendship represents a possibility for reflections that can improve leaders' metacognitive skills, which gives them opportunities for learning to develop their capacities in the process (Aas, Vennebo, and Halvorsen 2019), confirmed by the participants in this study.…”
Section: The Critical Friend As a Catalyst For Systematic Reflectionssupporting
confidence: 67%
“…By building learning centred around leaders' experiences and practices, theory and practice can be linked together through collaborative reflexive activities (Aas 2017a;Dempster, Lovett, and Fluckiger 2011;Huber 2011;Robertson 2013). In other words, school leaders being active and involved in development processes in their own schools is crucial to their personal and their schools' learning as well as for remaking practices (Aas, Vennebo, and Halvorsen 2019;Vennebo 2016). This corresponds to practical action research (Kemmis 2009), building on collaborative and self-reflective principles through which practitioners remake their practices for themselves.…”
Section: Introductionmentioning
confidence: 99%